2020
DOI: 10.1186/s12909-020-02334-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of general medicine rotation training on the in-training examination scores of 11, 244 Japanese resident physicians: a Nationwide multi-center cross-sectional study

Abstract: Background Although general medicine (GM) faculty in Japanese medical schools have an important role in educating medical students, the importance of residents’ rotation training in GM in postgraduate education has not been sufficiently recognized in Japan. To evaluate the relationship between the rotation of resident physicians in the GM department and their In-Training Examination score. Methods This study is a nationwide multi-center cross-sectional study in Japan. Participants of this study are Japanese j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…Our research was performed in a rural area (close to urban areas) that has one of the lowest physician/patient ratios, which might cause fragmentation of care [ 14 , 15 ]. To prepare for an aged society worldwide, increasing the number of general physicians could be vital to sustaining medical care for older patients with multimorbidity [ 35 , 36 ]. In other countries, family medicine education has been established, and this has dealt with the issues of multimorbidity and fragmentation of care [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research was performed in a rural area (close to urban areas) that has one of the lowest physician/patient ratios, which might cause fragmentation of care [ 14 , 15 ]. To prepare for an aged society worldwide, increasing the number of general physicians could be vital to sustaining medical care for older patients with multimorbidity [ 35 , 36 ]. In other countries, family medicine education has been established, and this has dealt with the issues of multimorbidity and fragmentation of care [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of resident physicians in university hospitals tends to be greater than in community-based hospitals, so the workload of each resident physician in a university hospital could be shorter than that of a resident physician in a community-based hospital. Moreover, I previously revealed that the amount of study time significantly associated with the GM-ITE score [ 7 ]. Several previous studies have also indicated the relationship between sufficient self-study time and professional development [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the mean GM-ITE scores of junior residents in university hospitals tend to be lower than those of community-based hospitals [ 7 ]. However, the difference in score was centered only on the total GM-ITE scores.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that medical students who chose general practice preferred frequent patient communication, engaging in clinical diagnostic reasoning, and community-oriented practice [9]. Additionally, other studies have revealed that relevant experiences in clinical settings along with having general physician role models were important for increasing students' interest in general medicine [10,11]. Based on the above, the research question of our study was: what prevents medical students from becoming general physicians?…”
Section: Introductionmentioning
confidence: 87%